Ligand substituent effect on the cytotoxicity activity of two new copper(ii) complexes bearing 8-hydroxyquinoline derivatives: validated by MTT assay and apoptosis in MCF-7 cancer cell line (human breast cancer). Issue 24 (16th April 2021) - Ali, Arif; Banerjee, Somesh; Kamaal, Saima; Usman, Mohammad; Das, Neeladrisingha; Afzal, Mohd; Alarifi, Abdullah; Sepay, Nayim; Roy, Partha; Ahmad, Musheer
Abstract : The presence of –COOH functionality in a copper(ii ) complex leads to higher cytotoxicity than that observed for a complex containing a –CN group. Abstract : In this study, we have examined the effect of ligand substituent on the structure–cytotoxicity relationships of the MCF-7 cancer cell line (human breast cancer), by two copper(ii ) complexes {[Cu(qmbn)(Hqmba)(q)]·NO3 ·2H2 O} (1 ) and {[Cu(Hqmba)2 (q)]·NO3 ·2H2 O} (2 ) (where, qmbn = 2-(quinolin-8-yloxy)(methyl) benzonitrile (L1 ); Hqmba = 2-((quinolin-8-yloxy)methyl)benzoic acid (L2 ) and q = quinolin-8-olate). The structural analysis reveals that both the complexes exhibit distorted octahedral (CuN3 O3 ) configuration which is further corroborated by density functional theory (DFT) calculations. The cytotoxicity impact of ligands (L1 and L2 ) and complexes (1 and 2 ) was screened against the MCF-7 cell line (human breast cancer). The MTT assay uptake indicated that the presence of –COOH functionality in complex 2 leads to higher cytotoxicity (lower IC50 ) than that observed for complex 1 containing a –CN group. This could be due to the strong H-bonding forming propensity of the carboxylic acids. Incubation of MCF-7 cancer cells with IC50 concentrations of 1 and 2 promoted cellular detachments via nuclear condensation and membrane destabilization followed by apoptosis as a result of metal-assisted generation of reactive oxygen species. Flow cytometry analysis showed that 1 and 2 might prompt early apoptosis in MCF-7 cells as the maximum percentage of cells appeared in the LR quadrant. Furthermore, mRNA expression analysis confirmed that both the complexes induced apoptosis in MCF-7 cells. Comparative mRNA expression analysis of complexes with their respective ligands also confirmed the enhanced apoptotic behavior of complexes. Furthermore, molecular docking studies of the complexes have also been performed with the active site of EGFR kinase receptors (major target for any cancer causing agent) due to similar analogues with FDA-approved EGFR inhibitors in order to rationalize its promising cytotoxicity activity.